Induction of Necrotic Cell Death and Activation of STING in the Tumor Microenvironment via Cationic Silica Nanoparticles Lead to Enhanced Antitumor Immunity - An, Myunggi (Nanoscale, 2018)
Nanotechnology has demonstrated tremendous clinical utility, with potential applications in cancer immunotherapy. Although nanoparticles with intrinsic cytotoxicity are often considered unsuitable for clinical applications, such toxicity may be harnessed in the fight against cancer. Nanoparticle associated toxicity can induce acute necrotic cell death, releasing tumor-associated antigens which may be captured by the antigen presenting cells to initiate or amplify tumor immunity. To test this hypothesis, cytotoxic cationic silica nanoparticles (CSiNPs) were directly administered into B16F10 melanoma implanted in C57BL/6 mice. CSiNPs caused plasma membrane rupture and oxidative stress of tumor cells, inducing local inflammation, tumor cell death and release of tumor-associated antigens. CSiNPs were further complexed with Bis-(3′–5′)-cyclic dimeric guanosine monophosphate (c-di-GMP), a molecular adjuvant which activates the stimulator of interferon genes (STING) in antigen presenting cells. Compared with unformulated c-di-GMP, delivery of c-di-GMP with CSiNPs markedly prolonged its local retention within the tumor microenvironment and activated tumor-infiltrating antigen presenting cells. Combination of CSiNPs and STING agonist showed dramatically increased expansion of antigen-specific CD8(+) T cells, and potent tumor growth inhibition in murine melanoma. These results demonstrate that cationic nanoparticles can be used as an effective in situ vaccine platform which simultaneously cause tumor destruction and immune activation.